Synthesis and application of amine and iminodiacetate chelating resin for removal of heavy metals from industrial wastewater - Wong, Hai Fatt (2013)
In this study, poly (glycidylmethachrylate-divinylbenzene) (PGMA-DVB) resins were synthesized by using suspension polymerization method. The modifications and optimization on cross-linked porous PGMA-DVB resin consisted of (i) Amination reaction using TAEA as an amine agent to produce amine resin, and Amine resin undergoes methylcarboxylation reaction to produce Iminodiacetate resin. Solid phase BC CP/MAS NMR analysis, thermogravimetric analysis, infrared analysis, CHN analysis and Scanning Electron Microscope (SEM) analysis were used to characterize the physical and chemical properties of the resins. The chemical shift graph of the synthesized resins obtained from the 13C CP/MAS NMR analysis showed that chemical structures of the synthesized amine and iminodiacetate resins in the laboratory were confirmed. In the thermogravimetry analysis, the thermogram of all the adsorbents in the temperature range of 30 - 420Â°C showed a maximum of weight loss indicating the loss of functional group and backbone from the resin. Infrared spectra of all the synthesized resins revealed the absorption frequency bands of carboxyl, amine, epoxy and C-H aliphatic in the range of 600-4000 cm-1. In the CHN analysis, carbon percent increased after amine reacted with sodium chloroacetate indicating that a new bonding was formed. SEM was used to determine the physical properties of synthesized resins where it was found that porosity of the amine and iminodiacetate resins are not significantly different. The amine resin binding capacities to Cu, Fe, Cd, Cr and Zn at optimum pH were 3.5, 0.82, 1.3, 2.4 and 3.19 mg g-1, respectively, compared to iminodiacetate resin: 8.48, 5.51, 2.8, 2.56 dan 1.43, respectively. It was also observed both resins have the high binding capacities were pH 5. The column method was used to determine the effectiveness of resin towards industrial wastewater containing metal ions. The study found that the performance of iminodiacetate resin on chromium-contaminated wastewater was better compared to the amine resin but vice-versa when applied on cyanide-contaminated wastewater. It is shown here that the amine and iminodiactate resins can be applied for wastewater treatment, however, their removal capacity varies depending on the type of polluted wastewater.